Haematological and biochemical changes after exposure to Maerua crassifolia ethanol leaf extract in rats - Akuodor Godwin Christian, Eban Linus Kechi, Nku Clement Oshie, Aja Daniel Ogbonna John, Ezeunala Mercy Nwakaego, Ajoku Gloria Ahunna, Nwobodo Ndubuisi Nwobodo (Journal of Applied Pharmaceutical Science, 2017)
This study was carried out to determine the safety profile of Maerua crassifolia by conducting the acute and subacute toxicological assay of its ethanol leaf extract in rats. The animals were treated daily with the leaf extract at doses of 100, 200 and 400 mg/kg orally for 14 and 28 days. Rats used as control were given distilled water and all rats weighed every 7 days. After the test, haematological and biochemical parameters as well as their relative organs weight were determined. There were no significant changes in body weight of treated animals compared to control in both studies. In the acute toxicity test, the extract did not cause any signs of toxicity or produce mortality in rats. Subacute results showed that oral administration of the leaf extract did not significantly (p
Keywords: Maerua crassifolia, Leaf extract, Haematological,Biochemical, organ weight, Rats.